An overview of the legal and cultural issues for migrant Muslim women of the European union: a focus on domestic violence and Italy - Bucci, Linda (Crime, law and social change, 2012)
The migration of Muslims into European nations and the intolerance exhibited towards them has been a growing challenge for the members of the European Union. The differences between the religion and cultures from which the Muslim women migrate and the receiving countries of the European Union may hamper the provision of social services to them when they experience domestic violence from their intimate partners. This article examines the potential for cross-cultural misunderstanding by examining domestic abuse in Italy in the context of both the social mores and the legal framework of that country. A comparison is made to the traditional perception of the role of women in Islamic culture. The research available on domestic violence in this context is examined as it relates to Italy and its Muslim migrants. The article suggests that what is needed are multidisciplinary cross-cultural solutions to provide services and meet the needs of Muslim victims of domestic violence in Italy.